Sequence variants at the TERT-CLPTM1L locus associate with many cancer types. - Rafnar, T; Sulem, P; Stacey, SN; Geller, F; Gudmundsson, J; Sigurdsson, A; Jakobsdottir, M; Helgadottir, H; Thorlacius, S; Aben, K; Blöndal, T; Thorgeirsson, T; et al. (2009)
The common sequence variants that have recently been associated with cancer risk are particular to a single cancer type or at most two. Following up on our genome-wide scan of basal cell carcinoma, we found that rs401681[C] on chromosome 5p15.33 satisfied our threshold for genome-wide significance (OR = 1.25, P = 3.7 x 10(-12)). We tested rs401681 for association with 16 additional cancer types in over 30,000 cancer cases and 45,000 controls and found association with lung cancer (OR = 1.15, P = 7.2 x 10(-8)) and urinary bladder, prostate and cervix cancer (ORs = 1.07-1.31, all P < 4 x 10(-4)). However, rs401681[C] seems to confer protection against cutaneous melanoma (OR = 0.88, P = 8.0 x 10(-4)). Notably, most of these cancer types have a strong environmental component to their risk. Investigation of the region led us to rs2736098[A], which showed stronger association with some cancer types. However, neither variant could fully account for the association of the other. rs2736098 corresponds to A305A in the telomerase reverse transcriptase (TERT) protein and rs401681 is in an intron of the CLPTM1L gene.